Population genetics of the endemic red-chested sea cucumber, Hemiocnus insolens, along the southern coastline of Africa - Ho, Yi-Ting (Department of Biological Sciences, 2024)
Hemiocnus insolens is the endemic red-chested sea cucumber (or holothuroid) of South Africa, found along the coastline spanning from Port Elizabeth, South Africa to Lüderitz, Namibia. They present as three colour variations (red, yellow, and white) prompting the existence of possible cryptic species. The aim of the study is to sequence the genomic markers of each colour variation using Sanger sequencing and metagenomic sequencing to analyse their phylogenetic and associated community structure to delimit whether the colour variations of H. insolens are a single species or a possible species complex. DNA was extracted from tissue of whole preserved (99% ethanol AR) samples and were sequenced for 16S rRNA and COI gene regions (Sanger sequencing) as well as their metagenomes (Oxford Nanopore Technologies). ChromasPro and seaview.exe were used for sequence analysis and tree building, respectively. MGnify and Flye were used for assessing the metagenomics of selected samples. Parsimony-based tree fitting was generated for 16S rRNA and COI which suggested that some differentiation between white samples, and red and yellow samples (BP = 100) (Figure 2.1, Figure 2.2). According to population genetics and phylogeography, these species can be considered as cryptic species due to their phylogeographic breaks bolstering the separation of certain colour variations. Metagenome-assembled genomes (MAGs) were used to further explore the community structure of each sample/colour variation and were holistically compared to the parsimony-based phylogenetic trees to support these differences and provide explanations. Results suggested some differences in gene expression and microbiome diversity between the colour variations; however, these results were preliminary as a result of small sample size and low throughput in sequencing. Metagenome studies provided some insight into creating a conceptual model of how the environment could affect the colour expression of H. insolens.